Design and Construction of a Website-Based Tourist Bus Rental System Using the Extreme Programming Method - Karima, Nida; Kurniawan , Defri (INOVTEK Polbeng - Seri Informatika, 2025)
Technological developments encourage companies to implement structured systems to improve operational efficiency. PMJ Trans, a tourist bus company located in Kudus, is faced with the problem of manual administrative data management, such as recording customer orders using Excel and inappropriate bus maintenance schedules. This study aims to design and build a website-based bus rental system using the XP method, which allows for short iterations and fast feedback. This system includes online booking features, booking history management, bus placement, and booking notifications from customers to admins. User Acceptance Testing (UAT) testing showed 100% system success, as measured by the aspects of Learnability, Efficiency, Memorability, Errors, and Satisfaction. The constraints during development were the limited number of respondents during the testing stage, where only the company owner was involved due to unsupportive time and location. Implementing this system can help the company's operational efficiency, reduce manual errors, and provide a good experience to customers. Further research suggests adding a payment feature integrated with the bank to automate payment confirmation and transaction security and a chatbot so that bookings via WhatsApp are well organised.